Perlindungan Tenaga Kerja Wanita Indonesia dalam Kasus Perdagangan Manusia di Kamboja - Eka An Aqimuddin; Fariz Farrih Izadi; Dhea Shabrina ‘Ishmah (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. Human trafficking is increasing because the profits obtained by the perpetrators are very large. Even according to the United Nations, human trafficking is the world's large's criminal enterprise which generates around 9.5 million USD in annual taxes. According to the results of a study by the International Labor Organization, the profits derived from trafficked women, men children are estimated at US 32 billion annually. Cambodia is a destination country for trafficking in persons with Indonesian victims having increased in recent years. Reports from Malaysia based on data for 2019 and 2020, in the border areas of neighboring Malaysia and Singapore show that more than 4,268 people come from Indonesia out of a total of 6,809 people who are involved in the crime of trafficking women in Malaysia as sex workers, while the results of monitoring submitted by US Department of State that out of 5 million migrant workers, 20% are the result of trafficking of women and children originating from Indonesia. The Asia Pacific Economic and Social Commission reports that Indonesia ranks third or lowest in efforts to tackle the problem of human trafficking and in 2017 Indonesia is in second place in the world as a victim of human trafficking. Abstrak. Perdagangan manusia semakin banyak dikarenakan keuntungan yang diperoleh pelakunya sangat besar. Bahkan menurut PBB, perdagangan manusia ini adalah sebuah perusahaan kriminal terbesar ketiga tingkat dunia yang menghasilkan sekitar 9,5 juta USD dalam pajak tahunan. Menurut hasil studi International Labour Organization keuntungan yang diperoleh dari perempuan, laki-laki dan anak-anak yang diperdagangkan diperkirakan mencapai US 32 miliar setiap tahunnya. Kamboja adalah negara tujuan perdagangan orang dengan korban Indonesia yang mengalami peningkatan dalam beberapa tahun terakhir. Laporan dari Malaysia berdasarkan data tahun 2019 dan 2020, di wilayah perbatasan negara tetangga Malaysia dan Singapura menunjukkan bahwa lebih dari 4.268 manusia berasal dari Indonesia dari sejumlah 6.809 manusia yang terlibat dalam kejahatan perdagangan perempuan di Malaysia sebagai pekerja seks, sedangkan dari hasil pemantauan yang disampaikan oleh US Department of State bahwa dari 5 juta buruh migran terdapat 20% merupakan hasil perdagangan perempuan dan anak berasal dari Indonesia. Adapun Economy and Social Commissionon Asia Pacific melaporkan bahwa Indonesia menempati peringkat ketiga atau terendah dalam upaya penanggulangan masalah perdagangan manusia dan pada tahun 2017 Indonesia adalah urutan ke dua di dunia jadi korban perdagangan manusia.